A Statistical Evaluation of the Occurence of Meningitis in Takum, Taraba State, Nigeria - Idi, Danjuma; Akobi, Clement; Stephen, Mathew; Bamigbala, Olateju Alao (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Meningitis remains a critical public health issue in Nigeria, particularly within the dry season when environmental factors such as low humidity and dust elevate transmission risks. Using historical incidence data from 2012 to 2021, this study utilizes the Autoregressive Integrated Moving Average (ARIMA) model estimate and predict the occurrence of meningitis occurrences. Findings frm the study revealed that the ARIMA(1,1,0) model emerged as the optimal fit, capturing the seasonal patterns and temporal trends in meningitis cases. This study recommends the integration of ARIMA-based forecasting into Nigeria’s public health strategies to strengthen early warning systems, optimize resource deployment, and enable more proactive responses during high-risk periods.